Free and Total Platelet Glycoprotein IIb/IIIa Measurement in Whole Blood by Quantitative Flow Cytometry during and after Infusion of c7E3 Fab in Patients Undergoing PTCA - Hézard, Nathalie; Metz, Damien; Nazeyrollas, Pierre; Nguyen, Philippe; Simon, Gérard; Daliphard, Sylvie; Droullé, Chantal; Elaerts, Jacques; Potron, Gérard (Thrombosis and Haemostasis, 1999)
A quantitative flow cytometry assay was used to evaluate the ex vivo kinetics of c7E3 Fab platelet effect in 16 patients undergoing PTCA treated with abciximab and compared with aggregometry assay. Immunolabeling of platelets was directly assessed on whole blood, using in parallel two monoclonal antibodies (Mabs) raised against GPIIIa, Mab1, the binding of which is inhibited by c7E3 Fab, and Mab2, the binding of which is not affected by c7E3 Fab. We found a severe and sustained inhibition of both GPIIb/IIIa receptors and platelet functions. The inter-individual variation in response to abciximab was low. A significant transient increase at H24 and H48 in the binding of Mab2 was found as an unexpected result, and confirmed in vitro. Results demonstrate that flow cytometry is a reliable method in agreement with aggregation. In addition, our results show that it is a standardized tool and a time-saving technique.